Root growth potential, variability and heritability of yemane (Gmelina arborea Roxb) in the Philippines (2012)
The experiment was undertaken to characterize root growth potential (RGP) and determine growth variability and heritability of eight hundred Yemane (Gmelina arborea Roxb) based on provenance in 3 provinces in the Philippines. Significant variations of morphological characteristics of seedlings of Yemane by seed sources were found in the study. Seed sources from Quezon and Cotabato Provinces differed in all morphological traits compared with the seed sources from Davao del Sur. The root growth potential in terms of the number of first order lateral roots (FOLR) was positively correlated with all seedlings morphological characters, such as root collar diameter, primary root length, stem height, and root:shoot ratio. The frequency distribution of FOLR groupings were established such as : R1 (0–10) ; R2 (11–20) ; and R3 (21–30+). The entire traits measured were genetically influenced by the seed sources based on observed high heritability estimates.